O nascimento de uma biblioteca comunitária: a contribuição dos projetos de promoção à leitura para a comunidade carente - BARRAL JUNIOR, Miguel Queiroz (2017)
It presents a case study about the Tralhoto Reader community library, located in the Itaiteua neighborhood, Outeiro district, Belém - Pará, informing about its need for a poor community. It addresses social projects for the dissemination of information and the role of the librarian as a transforming agent for society. Its main objective is to talk about encouraging reading to minimize social differences and strengthen access to education, using books as a main tool, associating cultural projects for children and young people in the region to arouse interest in knowledge. It is an exploratory research, with a qualitative approach, carried out through field research, aiming at a case study, through participant observation. It reports on the extension project created to organize the collection and analysis of the profile of the volunteers involved, conducting a predominantly qualitative questionnaire and analyzing the data obtained, including bibliographic research to support the creation of the project. It concludes that due to the lack of commitment of the public organizations with the peripheral districts, the individual initiative is one of the main reasons for the creation of community libraries.